The effect of soil compaction and moisture content on tillage stage in paddy / Tengku Mohamad Khushaire Tuan Mohd Zaki - Tuan Mohd Zaki, Tengku Mohamad Khushaire (Faculty of Plantation and Agrotechnology, 2019)
The Malaya’s rice economy developed significantly over the nineteenth century. The rice cultivation is the oldest a country agricultural industry because rice is a Malaysia's staple food. The land preparation stage in paddy have many procedures to follow in order to avoid future problem in term of lack growth paddy as well as to gain high yield. At initial stage, the ploughing process is very important because paddy cannot grow well in hard soil condition and need to get more nutrient to live. When there are no nutrient in soil, the paddy crop is difficult to grow and will die. The ploughing process need be done by tractor with implement disc plough and rotavator. This research aim is to study the effect of tillage on the soil condition before and after ploughing process at paddy field. This study has considered three parameters which are soil compaction, soil moisture content and soil pH. Besides that, this study to identify the change of soil compaction, soil pH and soil moisture content in each session of ploughing process. This study to identify the relationship between soil compaction and soil moisture content during first and second ploughing. There are positive relationship between soil compaction and soil moisture content. The higher soil compaction the lower soil moisture content and vice versa. This study to identify the change soil pH session before, first and second ploughing process in paddy field. The ploughing process does not give any changes on pH soil value. In this case study, the ploughing process only affected the soil condition and paddy yield.